Biochemical Stimulation of Immune Cells and Measurement of Mechanical Responses Using Atomic Force Microscopy. Issue 2 (1st February 2019) - Hu, Kenneth H.; Bruce, Marc A.; Liu, Jianwei; Butte, Manish J.
Abstract: This manuscript details methods to ligate cell‐surface receptors on live cells with precise spatiotemporal control using an atomic force microscope (AFM) to deliver ligands. This approach can be used to image cellular responses upon activating T cell receptors when the AFM is mounted on an optical microscope. Moreover, the AFM measures forces generated by the cell during the contact. Using AFM to trigger cellular responses adds an important capability to the field of mechanobiology. We describe how to incorporate anti‐CD3 antibodies or other molecules onto an AFM cantilever and how to use AFM to activate T cells. © 2019 by John Wiley & Sons, Inc.